Thermal inactivation kinetics of Bacillus cereus in Chinese rice wine and in simulated media based on wine components. (July 2018) - Lv, Ruiling; Chantapakul, Thunthacha; Zou, Mingming; Li, Man; Zhou, Jianwei; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: Chinese rice wine, a traditional wine widely consumed in China, is typically sterilized in light of its sublethal alcohol content and nutritional richness. Nevertheless, several foodborne pathogens have been detected in final products, of which Bacillus cereus is one of the most heat-resistant. To study the effects of the wine matrix on bacterial inactivation, simulated media were established based on the main characteristics of the wine, including glucose content (23.48 ± 0.86 g/L), alcohol content (17.0 ± 0.5%), pH (4.14 ± 0.06), and protein content. In Chinese rice wine, log counts declined to 5.79 after 1 min heat treatment at 60.0 °C, 4.99 at 70.0 °C, and 4.37 at 80.0 °C. The loss of viability was smaller in simulated media with protein and glucose than in sterile saline, implying that glucose and especially protein were protective. The inactivation kinetics of B. cereus vegetative cells were then assessed in these media, and modeled. Remarkably, thermal survival curves in Chinese rice wine and simulated media were linear and well-modeled by first-order kinetics with R 2 values 0.9501–0.9992. The data demonstrated that media with acidic pH were the most adverse environment against B. cereus, with D-value 0.61 ± 0.02 min at 60.0 °C. Similar values were obtained in media with 23.48 g/L glucose at 80.0 °C. Transmission electron micrographs showed heat-induced injuries in B. cereus through "coagulation" of the cytoplasmic content in all the media. Furthermore, modifications on the cell wall in acidic pH and alcohol media, leakage of cellular content observed in Chinese rice wine and glucose media. Conclusively, the results might help optimize the sterilization parameters to ensure the safety and quality of Chinese rice wine. Highlights: Simulated media were used to test the effects of wine components on sterilization. Thermal inactivation of B. cereus was well-modeled by first-order kinetics. Thermal resistance was significantly affected by components of Chinese rice wine. Protein and glucose were protective to the vegetative cells of B. cereus . Different thermal-induced morphological changes obtained in various simulated media.